International Accounting Standards Board: An examination of the main financial and accounting topics addressed in the literature related to the COVID-19 pandemic - Santos, M. R. C. (2022)
The International Accounting Standards Board (IASB) conducts very demanding and complex work to setting accounting standards. The outputs produced by this board and their acts have been scrutinized over the years, by practitioners and academics. This study aims to contribute to the knowledge on the role of IASB by unveiling the research trends addressing this group of accounting experts and its publications. Through the analysis of the bibliometric data related to COVID-19 issues, this study identifies the main topics addressed in the literature during this pandemic. The results contribute to assessing the research conducted in this field and for creating the future research agenda on addressing the role and impact of the IASB during health, social and economic crises.